P.113: Luminous‐efficiency Improvement of Photovoltaic‐device‐integrated Organic Light Emitting Diode with Dual‐function Guiding Mode Resonance Structure. Issue 1 (1st July 2013) - Shen, Chia‐Yu; Lin, Ming‐Yi; Chen, Yi‐Jiun; Lin, Hoang Yan
Abstract: One‐dimensional dual‐function guided‐mode‐resonance (DF‐GMR) filters are designed to be the common electrodes of OLEDs integrated with photovoltaic devices, and can also be utilized as color filters. This structure can enhance the luminous efficiency from 39.1% to 56.9%, increase the contrast ratio, and the color deviation is negligible.